(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2025)
This study examines the fatty acid profiles, phospholipid content, phytosterol composition, and sugar concentrations of the kernel and pulp of African black pear (Dacryodes edulis) in order to determine their chemical composition and quality criteria. The findings showed notable variations in the distribution of fatty acids, with the pulp displaying higher amounts of polyunsaturated fatty acids (PUFA, 20.8%) and the kernel having a larger quantity of saturated fatty acids (SFA, 40.37%) than the pulp (36.41%). Oleic acid (C18:1) and stearic acid (C18:0) were the predominant fatty acids in both the kernel and the pulp. Better cholesterol-lowering capability was suggested by the kernel’s greater hypocholesterolemic/hypercholesterolemic ratio (H/H) (5.74), compared to the pulp’s (3.47). Total phospholipid content which is dominated by phosphatidylcholine (PC) and phosphatidylethanolamine (PE), was higher in the pulp (483.34 mg/100 g) than in the kernel (427.82 mg/100 g), according to phospholipid analysis. The pulp had a higher concentration of phytosterols, especially sitosterol (125.2 mg/100 g) than the kernel (108.48 mg/100 g). The pulp’s greater glucose and fructose concentrations which contribute to its sweeter taste profile were shown by sugar analysis. These results highlight Dacryodes edulis’s nutritional and practical potential for use in foods and medicine. Bangladesh J. Sci. Ind. Res. 60(2), 73-82, 2025